Press to Success: Gd5FW3O16—The First Gadolinium(III) Fluoride Oxidotungstate(VI) - Dorn, Katharina V.; Hartenbach, Ingo (Crystals (Basel), 2019)
The gadolinium(III) fluoride oxidotungstate(VI), with the formula Gd5FW3O16, represents the first published fluoride-derivative of a rare-earth metal oxidotungstate. It is synthesized by a mixture of GdF3, Gd2O3, and WO3 at 800 °C and a pressure of 2 GPa with the help of a belt press. The title compound crystallizes in the monoclinic space group P21/c (no. 14) with four formula units per unit cell and the following lattice parameters: a = 539.29 (4), b = 1556.41 (12), c = 1522.66 (11) pm, and β = 93.452 (4). The crystal structure comprises five crystallographically distinguishable Gd3+ cations, which are surrounded by either oxide and fluoride anions (Gd1–3) or by oxide anions only (Gd4, Gd5), with coordination numbers ranging between seven and nine. The fluoride anions are trigonal non-planar coordinated by three Gd3+ cations (Gd1–3). The distorted [WO6]6− octahedra in this structure form isolates edge- and vertex-connected entities of the compositions [W2O10]8− and [W2O11]10−, respectively. According to the presented units, a structured formula can be written as Gd4[FGd3]2[W2O10][W2O11]2. The single-crystal Raman spectrum reveals the typical symmetric stretching vibration mode of octahedral oxidotungstate(VI) units at about 871 cm−1.